DISTRIBUTION OF THIRD MOLAR AGENESIS BASED ON SEX, JAW INVOLVEMENT, AND NUMBER OF MISSING TEETH - Andi Merry Andani; Cristiani Nadya Pramasari; Sylvia Agustin; Danial Danial; Nydia Hanan (FKG ULM, 2025)
Background: The third molar is the final tooth to emerge in the oral cavity, distinguished by variability in its developmental timing and the potential for its presence or absence, rendering it particularly susceptible to environmental fluctuations during odontogenesis. Consequently, the prevalence of third molar impaction or hereditary absence is the highest among all teeth. The third molar is linked to various clinical problems, such as impaction, ectopic eruption, hard and soft tissue disorders, and agenesis. Tooth agenesis refers to the congenital absence of one or more teeth and is among the most prevalent defects in individuals. Purpose: This study aimed at exploring the distribution of third molar agenesis cases according to gender, jaw involvement, affected side, and the quantity of missing teeth. Methods: This research employed a quantitative methodology characterized by a descriptive observational design. Data were acquired from secondary sources, comprising panoramic radiographs and medical data sourced from Wahab Sjahranie regional General Hospital (RSUD). Results: Agenesis's gender distribution showed more frequency in females (69.2%) than in males (30.8%). Agenesis mainly impacted the maxilla (44.2%), then the mandible (26.9%), then both jaws (28.8%). Furthermore, on the frequency of absent third molars, the most often occurring situation was the absence of one tooth (50.0%), followed by two teeth (28.8%), three teeth (9.6%), and four teeth (11.5%). Conclusion: The findings of this study demonstrate that third molar agenesis is more prevalent in females, predominantly occurs in the maxilla, is more frequently unilateral, and typically entails the absence of a single tooth. Keywords: agenesis, panoramic, third molar